CLIC4 abrogation promotes epithelial–mesenchymal transition in gastric cancer. (27th September 2019) - Wang, Baolong; Zheng, Jiqing; Chen, Qiongyuan; Wu, Chaofan; Li, Yangxin; Yu, Xi-Yong; Liu, Bin; Liang, Chun; Liu, Song-Bai; Ding, Hui; Wang, Shuochen; Xue, Ting; et al.
Abstract: Chloride intracellular channel protein 4 (CLIC4) has been implicated in different types of cancers, but the role of CLIC4 in the development of gastric cancer (GC) remains unknown. We analyzed the expression of CLIC4 in 102 pairs of gastric adenocarcinomas by western blot and real-time PCR. Our data revealed that the expression of CLIC4 is reduced in GC tumor tissues compared with adjacent normal tissues. The expression levels of CLIC4 correlate inversely with the clinical stage of GC. CLIC4 expression is lowest in MKN45 cells, which have the highest tumorigenic potential and express the highest levels of cancer stem cell markers CD44 and OCT4, compared with N87 and AGS cells. Exogenous overexpression of CLIC4 downregulated the expression of CD44 and OCT4, and inhibited migration, invasion and epithelial–mesenchymal transition (EMT). Moreover, anchorage-independent growth of GC cells was decreased and the cells became more sensitive to 5-fluorouracil and etoposide treatment when CLIC4 was overexpressed. The ability of N87 cells to form tumors in nude mice was enhanced when CLIC4 was silenced. We, for the first time, demonstrate that CLIC4 suppresses tumor growth by inhibiting cancer cell stemness and EMT. Abstract : We analyzed the expression of CLIC4 in 102 pairs of gastric adenocarcinomas by western blot and real-time PCR. We identified CLIC4 as a new marker in gastric cancer. CLIC4 suppresses tumor growth by inhibiting cancer cell stemness and epithelial–mesenchymal transition.